Laser Cleaning and Spectroscopy: A Synergistic Approach in the Conservation of a Modern Painting. (25th December 2006) - Melessanaki, K.; Stringari, C.; Fotakis, C.; Anglos, D.
Abstract : We present results from preliminary laser cleaning studies performed on a 20th century modern painting, in which laser-induced breakdown spectroscopy (LIBS) was employed for monitoring the progress of material removal. This synergistic approach, that combines laser ablation cleaning with spectroscopic control, is of obvious importance as it offers a reliable means of ensuring proper conservation and could be the basis of a standard protocol for laser-based restoration procedures.